(untitled) (Applied Biological Research, 2023)
The bioactive components of Melastoma malabathricum leaves and the chemical compositions of ethanol-based M. malabathricum leaf extract were studied using gas chromatography-mass spectrometry (GC-MS) analysis. Twelve compounds obtained were: phthalic acid hept-4-yl isobutyl ester, oleic acid, n-hexadecanoic acid, melezitose, hexadecanoic acid methyl ester, hexadecanoic acid ethyl ester, D-mannose, 9,10 secocholesta-5,7,10(19) triene-3,24,25, triol, (3β,5Z,7E), 2-myristynoyl pantetheine, propanamide, 3-[3,5di(tetra-butyl)-4hydroxyphenyl]-N-(2hydroxyethyl), cholesta 4,6- dien-3-ol and desulphosinigrin. These compounds were characterized and analyzed for sPLA2 inhibition by molecular docking using the standard inhibitors. Among these, 2-myristynoyl pantetheine showed better inter actions with sPLA2IIA enzyme with ‘e’ value of -8.62 (PubChem id: 535560), followed by desulphosinigrin (-7.19) and D-mannose (-4.96). ADME toxicity studies proved that 2-myristynoyl pantetheine is better for in vivo administration. The 2-myristynoyl pantetheine was found to exhibit anti-inflammatory activity.